Standardization of a common protocol for establishment and cryopreservation of ibroblast cell lines from different indigenous livestock species - Rekha Sharma,; Himani Sharma,; RAK Aggarwal,; PK Vij,; Sonika Ahlawat,; Th Randhir Singh,; NV Patil,; MS Tantia, (Journal of Livestock Biodiversity, 2025)
The majority of precious livestock genetic resources remain exposed to the vagaries of genetic erosion due to limitations of in situ conservation programs. Fibroblast bank offers a practical approach to preserve germplasm due to advancement of cell culture techniques. The objective of current study was to biologically develop, evaluate and cryopreserve the skin ibroblast cells of different Indian livestock species obtained using an ef icient, common protocol. Ear marginal tissues from Manipuri and Marwari horses (n=8) and Kutchi camel (n=6) were collected for this purpose. Primary culture and irst passage was done using ibroblast speci ic media (HiFibroXL™). Epithelial-like and ibroblast-like cells emerged from the tissue explant margins within 10-14 days of culture in both the species. Subsequent passaging of cells for both horse and camel was continued using DMEM+Ham's F12 (1:1) media with 10% FBS. Fibroblast cells showed typical fusiform morphology with centrally located oval nuclei. Cells exhibited radiating, lame like or whirlpool like migrating patterns and density dependent inhibition during cell proliferation. The growth curve at passage-4 represented typical Sshape as the cell population passed through a lag phase, a logarithmic phase and a plateau phase. Population doubling time varied between 27.9 to 31.37 hrs with multiplication rate of 0.76- 0.86 population doubling/24  hrs. The cells were cryopreserved from 3 to 6 passage stocking at least 75 cryogenically-preserved vials  (1×106cells/ml) per animal. The protocol was further validated in six more species, mithun, yak, buffalo, goat, sheep and donkey. It can be concluded that ibroblast cell culture can be established from eight different livestock species at a faster rate and in a cost effective manner following a single common protocol described in this paper.